Influence of Deposition Rate on Fatigue Behavior of 316L Stainless Steel Prepared via Hybrid Laser Wire Direct Energy Deposition - Md Abu Jafor; Ryan Kinser; Ning Zhu; Khaled Matalgah; Paul G. Allison; J. Brian Jordon; Trevor J. Fleck (Metals)
Hybrid additive manufacturing (AM) provides a unique way of fabricating complex geometries with onboard machining capabilities, combining both additive and traditional subtractive techniques and resulting in reduced material waste and efficient high-tolerance components. In this work, a hybrid AM technology was used to create 316L stainless steel (316L SS) components using laser-wire-directed energy deposition (LW-DED) coupled with a CNC machining center on a single platform. Fully reversed fatigue tests were completed to investigate the as-manufactured life span of the additively manufactured structures for three different deposition rates of 6.33 g/min, 7.12 g/min, and 7.91 g/min. High-cycle fatigue test results showed that the fatigue performance of the tested specimens is not dependent on the deposition rates for the investigated parameters, with specimens with a 7.12 g/min deposition rate showing comparatively superior behavior to that of the other deposition rates at higher stress amplitudes. Fractography analysis was used to investigate the fractured surfaces, showing that the crack initiation sites were predominantly near the edges and not affected by the volumetric defects generated during manufacturing. X-ray-computed tomography (X-ray CT) analysis quantified the effect of the as-manufactured porosity on fatigue behavior, showing that the amount of porosity for the build rates used was insufficient to have a substantial impact on the fatigue behavior, even as it increased with the deposition rate.